PASTORAL EM SITUAÇÃO DE RUA Análise das Ações Pastorais da Comunidade Metodista do Povo de Rua na Cidade de São Paulo 1992 2009 - Dias, Jorge Schütz (2010)
The population in street situation is an urban phenomenon, currently aggravated by aspects of social, economic, cultural nature which gathers people together regardless of age, ethnicity, educational level and gender, in social exclusion situation, prevented from income and supplying of their vital, cultural and social needs. In the condition of exceeding population, they face obstacles to the development of their intellectual, biological and cultural capabilities; to the fairness in guaranteeing civil, political and social rights; to the quality of life in harmony and well-being, aim of human beings and to the utter fulfillment of their citizenship. The Methodist Community of Street People - CMPR has found its space at the beginning of the 1990s, while the Town Hall of São Paulo, in the turn of Mayor Luiza Erundina, promoted through the Social Well Being Municipal Office, the census to know who was, how was living and how the street population in the city of São Paulo was perceived. In this context, the Korean Ebenezer Methodist Church every Sunday offered assistance to the population serving bread, coffee and milk, and chocolate milk in the region of Dom Pedro II Park. It was established the partnership for the creation of CMPR through the awakening of public power and the participation of the Korean Methodist Church through the Korean Cafe. It was fundamental the willingness of Bishops Nelson Campos Leite and Geoval Jacinto da Silva, both from the Third Ecclesiastical Region of the Methodist Church, who started the work using the institution of philanthropic nature of the Methodist Church, the AMAS Social Assistance Methodist Association. Thus, with headquarters in Bridge Pedroso and due to geographical proximity, the CMPR linked itself to the AMAS from the Methodist Cathedral of São Paulo, acting in three dimensions: (1) creation of Co-Existence House, (2) Sheltering in the winter period; (3) Creation of the Hostel. The Action Plan designed by CMPR that consolidated the creation of the Hostel, dates from the transition 1994/95 and it had as its basis the Social Creed, the Plan for the Life and Mission of the Methodist Church and the Action Plan forwarded to the City Hall, in the light of the social aspect of the Methodist movement from John Wesley, establishing that the overall goal of CMPR would be the redemption of the citizenship of the people who constitute the street people. In this dimension, the thesis is structured into five chapters, included field research that has been conducted with employees and former employees of CMPR, with the objective of gathering contents to analyse the pastoral actions of the CMPR from the perspective of religious praxis, considering the philosophical and educational.(AU)